LA LENGUA CIENTÍFICA DE GÉMINO. I. LA APORTACIÓN LÉXICA - Calderón Dorda, Esteban (Myrtia, 1998)
The language used by Geminus is a very specialized one, a Fachsprache that demostrates a tendency to adapt the speech to the needs of the matter to be exposed. The scientific language of Geminus has the three typical features of the exact language of speciality: a very detailed use of the linguistic elements in order to determine exactly the meanings; secondly, a development of special significances in certain words; and finally, the creation of a corpus of an independent vocabulary. In this article we focus on this last component: the lexicon of new creation comes into the sight in Geminus. In this sense, the Aristotelic influence on Geminus, through the teaching of Posidonius, is essencial.